Illuminating Plasmodium invasion by lattice-light-sheet microscopy - Ganter, Markus; Frischknecht, Friedrich (Trends in parasitology, 2021)
Plasmodium merozoites invade erythrocytes in a stepwise manner through ligand binding, calcium signaling, and membrane deformation. Using a recently developed light-sheet microscope, Geoghegan et al. investigated invasion with unprecedented temporal resolution. Their spectacular footage revealed roles for host cell cholesterol and pore formation at the parasite-host cell interface.